Impacts of transformational leadership on turnover intention of child welfare workers. (January 2020) - Park, Taekyung; Pierce, Barbara
Highlights: Distance leadership in public child welfare shapes organizational culture and climate. Effect of transformational leadership on turnover intention of child welfare workers. Effect of transformational leadership on organizational culture and climate. Effect of transformational leadership on organizational commitment in child welfare. Abstract: The high turnover rate among child welfare workers is a constant, well-documented issue. This study aimed to examine how organizational factors, particularly leadership, affect child welfare worker turnover intentions in order to help child welfare agencies establish a practice model that prevents the turnover of qualified workers. In order to do so, it is important to examine the effects of organizational commitment on employees' turnover intentions. A cross-sectional survey was distributed among workers in public child welfare agencies in a Midwestern state in the United States (N = 214). A path model was developed to test the direct and indirect effects of transformational leadership on the turnover intentions of child welfare workers using STATA. The survey results indicated that the transformational leadership styles of local office directors had direct and negative effects on child welfare workers' turnover intentions. Therefore, this study recommends that child welfare services provide local office directors with leadership training in order to reduce the preventable turnover of child welfare workers.